Management of the electronic clinical history and improvement of the quality of patient care in the dentistry department of the Hermilio Valdizan hospital - Gutierrez Samaniego, Ursula Margarita (2021)
Objective: To verify the direct linear dependence relationship of the implementation of the Electronic Health Record (EHR) in the Improvement of the Quality of Patient Care in the Dentistry Service at the Hermilio Valdizan Hospital (HHV). Design: Applied or practical type. Statistical analysis: Sperman's correlation coefficient. Materials and methods: Questionnaire application to 14 dental service personnel and surveys to 70 continuing patients during the period of December 2020 and January 2021. Results: there is sufficient statistical evidence at a significant high level of 85.5%, that the implementation of the Electronic Health Record (EHR) is linearly correlated with the improvement of the Quality of Care in the Dentistry Service. Conclusions: Prioritize the implementation of the HCE as a Pilot Plan and based on results on a larger scale, implement at the level of all the HHV services.